2010
DOI: 10.1002/ptr.3314
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effects of Lycium barbarum polysaccharides on the impaired reproductive system of male rats induced by local subchronic exposure to 60Co‐γ irradiation

Abstract: Lycium barbarum, a famous Chinese medicinal herb, has a long history of use in traditional medicine as an antioxidant and to promote sexual fertility. Polysaccharides are the most important functional constituents in L. barbarum fruits. In this study, male rats were exposed to subchronic (60)Co-γ irradiation to investigate the effects of LBP on sperm quantity and motility, sexual ability, serum hormone levels, oxidative status and testicular tissue DNA damage on days 1, 7 and 14 of treatment. It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…The ‘rescuing’ effect of LBP on male sexual behavior suggests that LBP may be useful to treat male sexual dysfunction. This notion agrees with previous studies in which castration and irradiation on reproductive tissues suppressed male mating behavior, while LBP improved the mating ability of the affected rats [11], [12]. Apart from behavioral aspect, LBP may exert its beneficial effects on the reproductive system at cellular level.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The ‘rescuing’ effect of LBP on male sexual behavior suggests that LBP may be useful to treat male sexual dysfunction. This notion agrees with previous studies in which castration and irradiation on reproductive tissues suppressed male mating behavior, while LBP improved the mating ability of the affected rats [11], [12]. Apart from behavioral aspect, LBP may exert its beneficial effects on the reproductive system at cellular level.…”
Section: Discussionsupporting
confidence: 92%
“…Daily consumption of wolfberry juice improves the well-being feeling towards sexuality, including increase in sexual activity and ability [3]. Several studies which focused on the reproductive system showed that LBP was beneficial to male reproduction in several aspects: first, the sexual performance of hemicastrated rats could be improved by LBP treatment [11]; second, the quality, quantity and motility of sperms were increased [12] after LBP treatment;,third, damage of testis and seminiferous epithelium by different insults, such as hyperthermia, H 2 O 2 and irradiation, were prevented by LBP [10], [11]; and finally, decreases in testosterone of hemicastrated or irradiated rats were reversed by LBP [11], [12]. These findings provided evidence to support the notion that LBP exerts therapeutic effects on male sexual performance and fertility, although the mechanisms underlying the effects remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…One of the Gouqi's main active ingredient is Lycium barbarum polysaccharide (LBP), which have shown multiple pharmacological activities such as hypolipidemic, antioxidant, anti-aging, antitumor, and immunomodulation et al [27,28]. A wide array of studies confirmed that sexual functionality, sperm quality as well as the serum endocrine hormone levels were significant improved after administration of LBP in rat in the following reproductive damage models such as corticosterone-induced inhibition of the sexual behavior [29], radiation-induced spermatogenic damage [30] and bisphenol A-induced testis spermatogenic injuries [31]. Based on the above considerations, we hypothesized that LBP might minimize fertility impairment in secondary complications of diabetes.…”
mentioning
confidence: 99%
“…The traditional therapeutic effects of goji have made the plantefic experiments. Several clinical studies, in vivo animal, and in vitro cell studies have reported the efficacy of goji (antioxidant effects) fore [1415161718192024]. …”
Section: Discussionmentioning
confidence: 99%
“…Dursun et al [18] demonstrated that ischemic injury with testes torsion was decreased by the goji extract treatment via peritoneal injection. Several studies reported that goji extracts have an antioxidant effect on the reproductive system of male rats [171920]. …”
Section: Introductionmentioning
confidence: 99%